2010
DOI: 10.1111/j.1939-1676.2009.0445.x
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Cardiac Defects in Neonatal Foals: 18 Cases (1992–2007)

Abstract: Background: Literature available regarding congenital cardiac defects in foals is limited to reports of individual cases or small case series.Objective: To describe the clinical, echocardiographic, and necropsy findings and breed predilection of congenital cardiac defects in neonatal foals.Animals: Eighteen foals o15 days of age with 1 or more congenital cardiac defects. Methods: Medical records of foals diagnosed with congenital cardiac defects at the William R. Pritchard Veterinary Medical Teaching Hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
82
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(86 citation statements)
references
References 27 publications
2
82
2
Order By: Relevance
“…Valvular abnormalities were identified in 8/18 foals; the tricuspid valve or valvular apparatus were affected in 6/8 foals. Interestingly, Arabians were overrepresented with 35% of the foals belonging to that breed, supporting previous reports in which a higher prevalence of congenital cardiac defects in Arabians was suspected [8]. The occurrence of multiple coexisting congenital cardiac abnormalities is common in horses.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Valvular abnormalities were identified in 8/18 foals; the tricuspid valve or valvular apparatus were affected in 6/8 foals. Interestingly, Arabians were overrepresented with 35% of the foals belonging to that breed, supporting previous reports in which a higher prevalence of congenital cardiac defects in Arabians was suspected [8]. The occurrence of multiple coexisting congenital cardiac abnormalities is common in horses.…”
Section: Discussionsupporting
confidence: 82%
“…The occurrence of multiple coexisting congenital cardiac abnormalities is common in horses. In one study, one-third of the foals were found to have multiple concurrent cardiac defects and tachycardia was also a very common clinical finding in affected animals [8].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It may occur as a single defect, although it is often encountered in certain congenital syndromes, such as the tetralogy of Fallot [11,15-17]. Arabian horses are predisposed to VSD [9]. Marr [37] reported that Welsh Mountain ponies were more predisposed than Thoroughbreds.…”
Section: Discussionmentioning
confidence: 99%
“…VSDs are classified according to their location [8]. It is the most commonly diagnosed congenital heart disease in horses, among which Arabian horses exhibit particular predisposition to this disorder [9]. It may occur as a single defect, but it is often a part of a complex congenital anomaly [10-14], among which the best known congenital syndrome is the tetralogy of Fallot [11,15-17].…”
Section: Introductionmentioning
confidence: 99%